The Effect of Profit Sharing Rate, Interest Rate, and FDR on Mudarabah Financing - Amelia Febrianti; Ardelia Septi Fadhilah; Itah Miftahul Ulum; Mardi Mardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Islamic banking represents an appropriate option for Muslims to adhere to the rules of Allah and avoid the issue of usury, while also offering a variety of services to facilitate transactions within the community. This study aims to examine the internal factor, specifically the profit-sharing rate and financing-to-deposit ratio (FDR), along with external factors, namely interest rates, that affect Mudharabah financing. The secondary data used in this study consists of time series data from the financial statements of Islamic commercial banks in Indonesia for the period 2017-2022. The research method employed for sample selection is purposive sampling, with SPSS version 23 used as the analytical tool. The results found that the profit-sharing rate negatively affects mudarabah financing, interest rates do not have a significant relationship with mudharabah financing, and the FDR also negatively affects mudharabah financing.